Optimal Spatial-Dynamic Management of Groundwater Conservation and Surface Water Quality with On-Farm Reservoirs. (November 2014) - Kovacs, Kent; Wailes, Eric; West, Grant; Popp, Jennie; Bektemirov, Kuatbay
Abstract : We examine how much on-farm reservoirs can increase groundwater quantity and improve surface water quality using a spatial-dynamic model of farm profit maximization in the Arkansas Delta. Sensitivity analysis of the farm profit objective by including the value of surface water quality and the groundwater buffer value evaluates how accounting for environmental value affects the optimal crop mix, water use, and farm profits. The best policy for a critical water resource area is to have the government cost share construction of on-farm reservoirs because groundwater conservation and surface water quality goals are achieved efficiently for a modest redistribution of income.